A Journey through the Gonadotropin-Inhibitory Hormone System of Fish - Muñoz-Cueto, José A.; Paullada-Salmerón, José A.; Aliaga-Guerrero, María; Cowan, Mairi E.; Parhar, Ishwar S.; Ubuka, Takayoshi (Frontiers in Endocrinology, 2017)
Gonadotrophin inhibitory hormone (GnIH) is a hypothalamic neuropeptide that belongs to the RFamide peptide family and was first identified in the quail brain. From the discovery of avian GnIH, orthologous GnIH peptides have been reported in a variety of vertebrates, including mammals, amphibians, teleosts and agnathans, but also in protochordates. It has been clearly established that GnIH suppresses reproduction in avian and mammalian species through its inhibitory actions on brain GnRH and pituitary gonadotropins. In addition, GnIH also appears to be involved in the regulation of feeding, growth, stress response, heart function and social behavior. These actions are mediated via G protein-coupled GnIH receptors (GnIH-R), of which two different subtypes, GPR147 and GPR74, have been described to date. With around 30,000 species, fish represent more than one-half of the total number of recognized living vertebrate species. In addition to this impressive biological diversity, fish are relevant because they include model species with scientific and clinical interest as well as many exploited species with economic importance. In spite of this, the study of GnIH and its physiological effects on reproduction and other physiological processes has only been approached in a few fish species, and results obtained are in some cases conflicting. In this review, we summarize the information available in the literature on GnIH sequences identified in fish, the distribution of GnIH and GnIH receptors in central and peripheral tissues, the physiological actions of GnIH on the reproductive brain-pituitary-gonadal axis, as well as other reported effects of this neuropeptide, and existing knowledge on the regulatory mechanisms of GnIH in fish.